La fuerza de los caminos sonoros: caminata y música en Qoyllurit’i - Mendoza, Zoila (2010)
Here I explore the intrinsic relationship that for the people of the district of Pomacanchi (Cusco) exists between walking to the sanctuary of the Lord of Qoyllurit’i and the music that accompanies them. My attention focuses on the relationship with the chakiri wayri melody and to a lesser extent with that called alawaru. In this intrinsic relationship between music and the walk, on the one hand, the primacy of the unity of the visual and the auditory in the Andean cognitive processes reveals itself. On the other hand, in exploring this relationship in the context of the walk a third sensorial dimension key to such cognitive processes appears clearly. It is the sense of kinesthesia or sensation of movement. In other words. The unity of the visual, the auditory and the kinesthetic is what makes the participation in the fiesta of the Lord of Qoyllurit’i a unique and unforgettable experience. The obvious primacy of the unity of these three senses in the experience of pilgrimage of the people of Pomacanchi to the sanctuary of the Lord of Qoyllurit’i is not unique or exclusive of this festive context or of Pomacanchi. Simply, this experience allows us to analyze more closely a phenomenon that I believe to be spread in the Andes.